Human Resource Management Practices and Firm Innovation: A Study of Technology Startups in Kenya - Wafula, Lukas (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the human resource management practices and firm innovation: a study of technology startups in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In technology startups in Kenya, recruitment strategies drive product innovatio44n by attracting diverse talent, while training initiatives enhance process innovation by improving technical skills. Performance appraisals promote organizational innovation by recognizing innovative contributions, fostering a culture of continuous improvement. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, social exchange theory & diffusion of innovation theory may be used to anchor future studies on the human resource management practices and firm innovation: a study of technology startups in Kenya. Technology startups should prioritize employee development and learning initiatives to nurture a culture of innovation and continuous improvement. Policymakers should create a supportive regulatory environment that encourages innovation and entrepreneurship in Kenya's technology startup ecosystem.